Timing matters: Otological symptoms and Parkinson's disease. (September 2021) - Mahajan, Abhimanyu; Marsili, Luca; Dwivedi, Alok K.; Situ-Kcomt, Miguel; Grimberg, Maria B.; Wachter, Nathan; Abdelghany, Elhusseini; Duque, Kevin R.; Espay, Alberto J.
Abstract: Introduction: Otological symptoms contribute to the disability of established Parkinson's disease (PD). We sought to evaluate whether prodromal onset may affect PD progression. Methods: A retrospective cohort design was used to compare time to advanced disease, defined as a Hoehn & Yahr stage ≥3 in consecutive PD patients with history of auditory and/or vestibular symptoms appearing before versus after PD onset. Time from PD onset to H&Y ≥ 3 was determined using Cox proportional hazards, with adjusted results summarized as hazards ratio (HR). Results: After adjusting for age at PD onset, there was a lower risk of progression to advanced disease in patients with prodromal otological symptoms compared to those with otological symptoms after PD onset (HR = 0.34; 95%CI: 0.15–0.75, p = 0.008). This association remained significant after adjusting for age at PD onset and MDS-UPDRS III (HR = 0.25; 95% CI: 0.10–0.63, p = 0.003) and propensity score-adjusted analysis (HR = 0.46; 95% CI: 0.24–0.91, p = 0.025). Conclusion: Prodromal otological symptoms might be associated with a reduced risk of motor progression in PD. Highlights: We evaluated the effect of otological symptoms on PD progression using a retrospective cohort-design. From 188 consecutive eligible PD patients, 91 had otological symptoms and 97 did not. There was a lower risk of progression in patients whose otological symptoms appeared before compared to after PD onset. This novel observation is of unclear biological significance and further studies are warranted.